The Influence of the Secular Perturbation of an Intermediate-mass Companion. II. Ejection of Hypervelocity Stars from the Galactic Center - Zheng, Xiaochen; Lin, Douglas N. C.; Mao, Shude (The Astrophysical journal, 2021)
There is a population of stars with velocities in excess of 500 km s −1 relative to the Galactic center. Many, perhaps most, of these hypervelocity stars (HVSs) are B stars similar to the disk and S stars in a nuclear cluster around a supermassive black hole (SMBH) near Sgr A ⋆ . In Paper I of this series, we showed that the eccentricity of the stars emerged from a hypothetical disk around the SMBH that can be rapidly excited by the secular perturbation of its intermediate-mass companion (IMC), and we suggested IRS 13E as a potential candidate for the IMC. Here we show that this process leads to an influx of stars on parabolic orbits to the proximity of Sgr A ⋆ on a secular timescale of a few megayears. This timescale is much shorter than the diffusion timescale into the lost cone through either the classical or the resonant relaxation. Precession of the highly eccentric stars’ longitude of periastron, relative to that of the IMC, brings them to its proximity within a few megayears. The IMC’s gravitational perturbation scatters a fraction of the stars from nearly parabolic to hyperbolic orbits with respect to the SMBH. Their follow-up close encounters with the SMBH induce them to escape with hypervelocity. This scenario is a variant of the hypothesis proposed by Hills based on the anticipated breakup of some progenitor binary stars in the proximity of the SMBH, and its main objective is to account for the limited life span of the known HVSs. We generalize our previous numerical simulations of this process with a much wider range of orbital configurations. We demonstrate the robustness and evaluate the efficiency of this channel of HVS formation. From these numerical simulations, we infer observable kinematic properties for the HVSs.